Rankings and entrepreneurial higher education - Celeste, Letícia Fernandes Costa; da Silva, Carlos Eduardo Sanches; Mello, Carlos Henrique Pereira (Frontiers in Education, 2025)
This literature review provides readers with a synthesis of current information about university rankings, including those related to academic entrepreneurship, which serve as a means of monitoring third mission efforts in Higher Education Institutions (HEIs). By conducting a thorough search on Scopus and Web of Science databases, relevant studies were selected based on specific criteria. The review suggests that rankings directly impact the governance of HEIs. Due to the disparate nature of third mission university activities, having a ranking system for universities based on these specific types of activities could provide government policymakers with a greater understanding of the strengths of universities across a new range of metrics. The findings highlight that there is still no common framework of criteria for evaluating and measuring the performance of entrepreneurial universities and the engagement of academics with third mission activities. Addressing this issue is crucial because entrepreneurial education alone does not significantly influence students’ intentions to pursue entrepreneurship and start new businesses. By creating incubators and providing financial resources, consultancy and access to technological tools, universities encourage and support their students’ entrepreneurial intentions, diversify their funding sources and enhance their innovation and profitability. Academic entrepreneurship rankings can help universities develop appropriate institutional settings to achieve these goals and to produce individuals capable of leading social and economic progress.